Targeting Glioblastoma Using a Novel Peptide Specific to a Deglycosylated Isoform of Brevican. Issue 4 (20th January 2021) - von Spreckelsen, Niklas; Fadzen, Colin M.; Hartrampf, Nina; Ghotmi, Yarah; Wolfe, Justin M.; Dubey, Shipra; Yang, Bo Yeun; Kijewski, Marie F.; Wang, Shuyan; Farquhar, Charlotte; Bergmann, Sonja; Zdioruk, Mykola; et al.
Abstract: Glioblastoma (GBM) is the most common and deadliest form of brain tumor and remains amongst the most difficult cancers to treat. Brevican (Bcan), a central nervous system (CNS)‐specific extracellular matrix protein, is upregulated in high‐grade glioma cells, including GBM. A Bcan isoform lacking most glycosylation, dg‐Bcan, is found only in GBM tissues. Here, dg‐Bcan is explored as a molecular target for GBM. In this study, a d ‐peptide library is screened to identify a small 8‐amino acid dg‐B can‐T argeting P eptide (BTP) candidate, called BTP‐7 that binds dg‐Bcan with high affinity and specificity. BTP‐7 is preferentially internalized by dg‐Bcan‐expressing patient‐derived GBM cells. To demonstrate GBM targeting, BTP‐7 is radiolabeled with 18 F, a radioisotope of fluorine, and increased radiotracer accumulation is found in intracranial GBM established in mice using positron emission tomography (PET) imaging. dg‐Bcan is an attractive molecular target for GBM, and BTP‐7 represents a promising lead candidate for further development into novel imaging agents and targeted therapeutics. Abstract : Here, the discovery of a novel peptide, called dg‐Bcan‐Targeting Peptide (BTP)‐7, that can selectively home in on glioblastoma (GBM) cells, is described. Extensive characterization of the peptide through binding kinetic analyses and cell uptake tests demonstrate its potential for targeting dg‐Bcan and GBM cells. Radiolabeling of BTP‐7 with 18 F enables PET imaging of intracranial xenograft GBM in mice.